2022
DOI: 10.1093/icc/dtac056
|View full text |Cite
|
Sign up to set email alerts
|

Structural change, productive development, and capital flows: does financial “bonanza” cause premature deindustrialization?

Abstract: Recent contributions to the literature on industrialization and development have confirmed that manufacturing continues to play a key role as a driver of economic development. As a corollary, these contributions highlight the importance of premature industrialization as a barrier to economic development and as one of the main sources of the middle-income trap. In this paper, we analyze the factors that may have hindered industrial development in the past four decades. In particular, we focus on the role of (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Additionally, the credit expansion arising from external capital inflows contributed to asset price inflation, particularly financial and real estate (Aliber and Kindleberger 2015). As a result, the balance-sheets of firms in non-tradable sectors were "artificially" inflated, which facilitated further financing and a further shift of capital and labor towards these sectors (Botta, Yajima, and Porcile 2022). In this way, financial flows contributed to the increase in the expected return on investments in non-tradable sectors.…”
Section: Dutch Disease: Causality Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the credit expansion arising from external capital inflows contributed to asset price inflation, particularly financial and real estate (Aliber and Kindleberger 2015). As a result, the balance-sheets of firms in non-tradable sectors were "artificially" inflated, which facilitated further financing and a further shift of capital and labor towards these sectors (Botta, Yajima, and Porcile 2022). In this way, financial flows contributed to the increase in the expected return on investments in non-tradable sectors.…”
Section: Dutch Disease: Causality Channelsmentioning
confidence: 99%
“…Other literature emphasizes the thesis that there is greater potential for productivity growth in tradable sectors, particularly in manufacturing (e.g., Szirmai 2012;Tregenna 2009;Rocha 2018;Rodrik 2016). Botta, Yajima, and Porcile (2022) empirically analyzed the impact of capital inflows (foremost, portfolio investment and external lending) and argued that the recipient economies could suffer from financial Dutch disease-like transmission mechanism. The capital inflows from abroad would cause the decline in the technological level of the production of goods and the shift of resources towards non-tradable goods, particularly with the deterioration in the production of technological-intensive tradable goods.…”
Section: Dutch Disease: Causality Channelsmentioning
confidence: 99%
“…Ravindran and Babu (2021) identified the rise of income inequality with premature deindustrialization in case that workers are absorbed into low-productive and informal market services. Botta et al (2022) found that net capital inflows are as a potential source of premature deindustrialization.…”
Section: Literature Review and Study Contributionsmentioning
confidence: 99%
“…The driving force behind structural transformation is the productivity of the modern sector, which includes manufacturing and services [ 5 ]. According to estimates from the World Bank [ 1 ], the share of manufacturing in GDP, which averaged 16.13% in 1990, declined to 13.93% in 2000 and further decreased to 11.17% in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the presence of productivity gaps in the region. Existing literature suggests that shifting from a subsistence/agrarian and resource-extractive economy to a more manufacturing and services-oriented one plays a crucial role in driving economic growth and enhancing productive capacity [ 5 , 6 ]. Manufacturing, in particular, offers unique advantages such as capital accumulation, economies of scale, and technological advancements, making it a preferred avenue for improving productivity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%